2010
DOI: 10.1098/rspb.2010.2037
|View full text |Cite
|
Sign up to set email alerts
|

A latitudinal gradient in rates of evolution of avian syllable diversity and song length

Abstract: We ask whether rates of evolution in traits important for reproductive isolation vary across a latitudinal gradient, by quantifying evolutionary rates of two traits important for pre-mating isolation-avian syllable diversity and song length. We analyse over 2500 songs from 116 pairs of closely related New World passerine bird taxa to show that evolutionary rates for the two main groups of passerines-oscines and suboscines-doubled with latitude in both groups for song length. For syllable diversity, oscines (wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 47 publications
(57 reference statements)
8
97
5
Order By: Relevance
“…The duration of the warble part was positively correlated with latitude, which is in line with expected elaboration in more seasonal and unpredictable habitat with presumable stronger sexual selection pressures (c.f. Catchpole 1982;Irwin 2000;Botero et al 2009;Weir and Wheatcroft 2011). However, at the same time we found the number of different element types of the warble part to be negatively correlated with latitude.…”
Section: Complex Divergence Patterns Across Latitudecontrasting
confidence: 43%
See 2 more Smart Citations
“…The duration of the warble part was positively correlated with latitude, which is in line with expected elaboration in more seasonal and unpredictable habitat with presumable stronger sexual selection pressures (c.f. Catchpole 1982;Irwin 2000;Botero et al 2009;Weir and Wheatcroft 2011). However, at the same time we found the number of different element types of the warble part to be negatively correlated with latitude.…”
Section: Complex Divergence Patterns Across Latitudecontrasting
confidence: 43%
“…Sedentary populations may also have more convergent songs through copying of neighbourhood songs, at least in some species, driven by the higher consistency in the identity of neighbouring males (Kroodsma 1999). Furthermore, variation in habitat density and species diversity may yield variable competition for acoustic space, and thereby allow song elaboration more easily at relatively high latitudes, where vegetation is typically less dense and acoustic competition with other species less intense (Weir and Wheatcroft 2011;Singh et al 2015). Several comparative studies have confirmed positive correlations between song elaboration and latitude, both among (Catchpole 1982;Botero et al 2009) and within species (Collins et al 2009;Kaluthota et al 2016).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Irwin 2000, Mahler & Gil 2009, Weir & Wheatcroft 2011, Cardoso et al 2012; Table 1). Hypotheses proposed to explain this variation invoke both ecological selection (Weir et al 2012) and sexual selection (Catchpole 1982) as the causes of these patterns (Table 2).…”
Section: Latitudinal Effectsmentioning
confidence: 99%
“…In the years since Catchpole (1982) hypothesized that migratory songbird species might be expected to sing more elaborate songs than nonmigratory species, several broad comparative studies have found a positive association between song elaboration and migratory distance (Read andWeary 1992, Mountjoy andLeger 2001) or breeding latitude (Botero et al 2009, Mahler and Gil 2009, Weir and Wheatcroft 2011, Cardoso et al 2012, Greig et al 2013). These empirical findings are intriguing, but they are also puzzling, because it is not clear why migration and song elaboration would be linked.…”
Section: Introductionmentioning
confidence: 99%